UPAYA MENINGKATKAN HASIL BELAJAR MEMBACA PEMAHAMAN BAHASA INGGRIS TEXT REPORT MELALUI METODE COOPERATIVE LEARNING TIPE TALKING STICK - Yulia Afrina (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research was conducted based on learning outcomes of English of students class IX are always bad. Every time,they always seem boring and unable to answer the question, so the classroom becomes noisy. This study aims to: (1) find theproblem and find a solution so that the learning process fun and not boring for students, (2) improving the learning outcomes ofstudents of class IX 1 in English Learning aspect reading comprehension. This research was conducted at the Junior High School 43 palembang in October 2011 until Januari 2012. This study used action research method in 2 cycles and each cycle consisted of 3meetings. The instrument used in this method was:  a written test to determine the ability of reading comprehension,observation sheets, field notes. The results of this study showed that in the fisrt cycle the average percentage of students who have completed 84,21%, the second cycles of the average percentage of students who have completed 97,38%.This was in accordance with pre-determined indicators of success namely the success percentage of average of at least 75%. The conclution of this research that the ability of reading comprehension using Cooperative Learning Method Talking Stick Type in class IX 1 SMP Negeri 43 Palembang. can improve student’s ability in reading comprehension.